If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 5x = -3x + -12 Reorder the terms: 4 + 5x = -12 + -3x Solving 4 + 5x = -12 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 4 + 5x + 3x = -12 + -3x + 3x Combine like terms: 5x + 3x = 8x 4 + 8x = -12 + -3x + 3x Combine like terms: -3x + 3x = 0 4 + 8x = -12 + 0 4 + 8x = -12 Add '-4' to each side of the equation. 4 + -4 + 8x = -12 + -4 Combine like terms: 4 + -4 = 0 0 + 8x = -12 + -4 8x = -12 + -4 Combine like terms: -12 + -4 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| 2*sqrt(2)*x=ln(x^2-1) | | 9(11-m)=5(m-7) | | xdy-ydx=0 | | 2n-18=2n | | 8x(8x-5)(5x+9)=0 | | (X+24)+x=90 | | 2x-7-7x+3= | | lx-2l=6 | | 3x+90y=330-10x-6y=-440 | | -5(y+2)=20 | | 7(4n-1)(2n+11)=0 | | x^2-11x-18=3x+2 | | 7y-7=5y-3 | | 2(2y-1)(y+5)+y(y+5)=0 | | 18(v+1)-2v=4(v+2)-11 | | 7x-4(x-4)+20=25 | | 4z^2(2z+9)(9z-2)=0 | | 3x+12=-4x-9 | | 4x=13x-234 | | 3(x-5)+2x=x+11 | | 2y(y+3)=(4y-2)(y+5)+y(y+5) | | (7m+16)(7-16)=0 | | 2x+3-4x=5x-6 | | 6x+108=9x | | -3x(3x+8)(x-5)=0 | | 9y+5=17 | | 5x+9=-46-6x | | 2x-3=-5(x-4) | | 5(x-3)-(3x-7)= | | 18x^2-27x=3x^3 | | -x^8+(8x)-24=0 | | -3(k-7)(8k+3)=0 |